2019
DOI: 10.1007/s42452-019-1398-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature synthesis of nanoscale BaTiO3 powders via microwave-assisted solid-state reaction

Abstract: Microwave-assisted solid-state reactions (MSSR) are investigated for their ability to synthesize nanocrystalline BaTiO 3 powders at low temperatures. Ba(OH) 2 •H 2 O and TiO 2 •xH 2 O are, respectively, initial precursors for Ba and Ti. In this study, these precursors were mixed according to their chemical stoichiometry and heated in a temperature range of 100-1000 °C by MSSR. Nanocrystalline BaTiO 3 powders having an average size of 26 nm were produced by MSSR, even at 100 °C. The crystallization-related acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…Therefore, precursors having hydroxyl and water molecules are potential candidates for powder synthesis via MWH. Our previous preliminary research on the application of microwave irradiation in the synthesis of BaTiO 3 powders [ 15 ] confirmed that initial sources having hydroxyl and water molecules had a lower synthesis temperature compared to those without polar radicals.…”
Section: Introductionmentioning
confidence: 95%
“…Therefore, precursors having hydroxyl and water molecules are potential candidates for powder synthesis via MWH. Our previous preliminary research on the application of microwave irradiation in the synthesis of BaTiO 3 powders [ 15 ] confirmed that initial sources having hydroxyl and water molecules had a lower synthesis temperature compared to those without polar radicals.…”
Section: Introductionmentioning
confidence: 95%
“…To enhance the microstructural uniformity of BaTiO 3 -based ceramics, various aspects of BaTiO 3 , such as synthesis procedures [10], sintering conditions [11], and nanostructural properties [12], have been studied. In particular, many researchers have investigated advanced synthetic methods, including the solid-state reaction (SSR) and sol-gel method, to prepare BaTiO 3 powder with fine particles and high crystallinity [13].…”
Section: Introductionmentioning
confidence: 99%